A Detailed Analysis of the KDD CUP 99 Data Set (Eurasian Research Bulletin, 2022)
During in last decade, anomaly detection It has attracted the attention of many researchers to overcome the weakness of signature-based IDS in detecting new attacks, and KDDCUP'99 is the most widely used dataset for grade from these systems. Having held a statistical analysis of this data set, we found two important issues that greatly affects the performance of the systems being evaluated, and the resultsin a very poor evaluation of anomaly detection approaches. To to solve these problems, we proposed a new dataset, NSL-KDD, which the consists from selected records from in full KDD datainstalled as well as does No suffer from Any from mentioned limitations